Jump Processes in Natural Gas Markets - Charles F. Mason; Neil Wilmot (Center for Economic Studies and ifo Institute (CESifo), 2014)
Natural gas is likely to become increasingly important in the future. Understanding the stochastic underpinnings of natural gas prices will be critical, both to policy analysts and to market participants. To this end, we investigate the potential presence of jumps in natural gas spot prices in the U. S. and in the U. K. We find compelling empirical evidence for the importance of jumps in both markets, though jumps appear to appear more frequently in the U. K. Some of the difference between the U.S. and U.K. jump probabilities may be due to oil prices, other factors play a role.
Keywords: Q41; G17; 330; natural gas prices; jump diffusion; GARCH